Jewish feminism: framed and reframed - Fuḳs, Ester (Feminist studies and sacred texts series, 2018)
Jewish feminism framed -- Jewish feminist scholarship: the liberal frame -- Jewish feminist theory: the personal frame -- The new Jewish studies: the masculinist frame -- Women and Holocaust studies: the essentialist frame